Practical Hadoop migration : how to integrate your RDBMS with the Hadoop ecosystem and re-architect relational applications to NoSQL /: how to integrate your RDBMS with the Hadoop ecosystem and re-architect relational applications to NoSQL. (2016) - Lakhe, Bhushan
No abstract available